Twelfth night [Večer trojkráľový anglicky] - Shakespeare, William, 1564-1616 (A Shakespeare children's story, 2020)
Twelfth Night by William Shakespeare is a delightful comic love story. The play begins with a shipwreck, during which Viola, a young aristocratic-born woman, is separated from her identical twin brother, Sebastian, and is swept onto the shores of the Kingdom of Illyria. Thus begins this entertaining tale of mistaken identities and thwarted love.